How Pediatric Surgeons Use Social Media to Attract New Patients - Romano, Ron; Baum, Neil (European Journal of Pediatric Surgery, 2014)
Social media has changed the landscape of online interaction for all doctors including pediatric surgeons. Of course the public including our patients and potential new patients having immediate access to these sites through mobile devices and iPads has contributed immensely to this phenomenon. Nonetheless, it seems that we are all rushing to get in front of our target audience and to engage in a relationship with them in a cost-effective fashion. This article will discuss the role of the Internet and media and how you can use this technology to attract new pediatric patients to your practice.
Keywords: social media; Internet; Facebook; Twitter; YouTube; Google